Biochemical assessment of serotonergic and cholinergic dysfunction and cerebral atrophy in Alzheimer's disease. - Bowen, D; Allen, S; Benton, J; Goodhardt, M; Haan, E; Palmer, A; Sims, N; Smith, C; Spillane, J; Esiri, M; Neary, D; Snowdon, J; et al. (1983)
Markers of serotonin synapses in entire temporal lobe and frontal and temporal neocortex were examined for changes in Alzheimer's disease by use of both neurosurgical and autopsy samples. Uptake of [3H]serotonin, binding of [3H]imipramine, and content of indolamines were all significantly reduced, indicating that serotonin nerve terminals are affected. Binding of [3H]serotonin was also reduced, whereas that of [3H]quinuclidinyl benzilate, [3H]muscimol, and [3H]dihydroalprenolol were unaltered. When the Alzheimer's samples were subdivided according to age, the reduction in [3H]serotonin binding was a feature of only autopsy samples from younger patients. In contrast, presynaptic cholinergic activity was reduced in all groups of Alzheimer's samples, including neurosurgical specimens. Five markers, thought to reflect cerebral atrophy, cytoplasm, nerve cell membrane, and neuronal perikarya were measured in the entire temporal lobe. In Alzheimer's disease the reductions (mean 25%, range 20-35%) were thought to be too large to be due only to loss of structures associated with the presumed cholinergic perikarya in the basal forebrain and monoamine neurones in the brain stem.